Vascular Development in the Zebrafish - Gore, Aniket V. (Cold Spring Harbor Laboratory Press, 2012)
The zebrafish has emerged as an excellent vertebrate model system for studying blood and lymphatic vascular development. The small size, external and rapid development, and optical transparency of zebrafish embryos are some of the advantages the zebrafish model system offers. Multiple well-established techniques have been developed for imaging and functionally manipulating vascular tissues in zebrafish embryos, expanding on and amplifying these basic advantages and accelerating use of this model system for studying vascular development. In the past decade, studies performed using zebrafish as a model system have provided many novel insights into vascular development. In this article we discuss the amenability of this model system for studying blood vessel development and review contributions made by this system to our understanding of vascular development.